The Firehawk Stent: A Review of a Novel Abluminal Groove-Filled Biodegradable Polymer Sirolimus-Eluting Stent. Issue 4 (July 2020) - Saito, Yuichi; Grubman, Daniel; Cristea, Ecaterina; Lansky, Alexandra
Abstract : Despite recent advances in drug-eluting stent (DES) technology, late adverse events remain concerns after percutaneous coronary intervention. The persistence of polymer material on DES has been suggested as a trigger for chronic inflammation. The Firehawk, a novel DES, has a unique design with recessed abluminal grooves, to which sirolimus and biodegradable polymer are applied. The Firehawk stent is designed to minimize polymer volume and antiproliferative drug concentration to reduce inflammation and hypersensitivity reactions. Several recent trials have reported the clinical outcomes of this device. This article provides a review of the current clinical evidence concerning the Firehawk stent.